2021
DOI: 10.3389/fphar.2021.654445
|View full text |Cite
|
Sign up to set email alerts
|

ATP and Adenosine in the Retina and Retinal Diseases

Abstract: Extracellular ATP and its ultimate degradation product adenosine are potent extracellular signaling molecules that elicit a variety of pathophysiological pathways in retina through the activation of P2 and P1 purinoceptors, respectively. Excessive build-up of extracellular ATP accelerates pathologic responses in retinal diseases, whereas accumulation of adenosine protects retinal cells against degeneration or inflammation. This mini-review focuses on the roles of ATP and adenosine in three types of blinding di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Under pathological conditions, such as elevated intraocular pressure in glaucoma, P2 × 7R is upregulated, causing retinal neuronal damage. The P2 × 7R antagonists, BBG and MRS2540, prevent neuronal death induced by age-related macular degeneration, glaucoma, and diabetic retinopathy [ 80 ]. In addition to causing tissue damage under pathological conditions, P2 × 7R also plays other roles in the nervous system.…”
Section: P2 × 7r: Distribution and Role In The Nervous Systemmentioning
confidence: 99%
“…Under pathological conditions, such as elevated intraocular pressure in glaucoma, P2 × 7R is upregulated, causing retinal neuronal damage. The P2 × 7R antagonists, BBG and MRS2540, prevent neuronal death induced by age-related macular degeneration, glaucoma, and diabetic retinopathy [ 80 ]. In addition to causing tissue damage under pathological conditions, P2 × 7R also plays other roles in the nervous system.…”
Section: P2 × 7r: Distribution and Role In The Nervous Systemmentioning
confidence: 99%
“…Actually, pharmacological treatments have been utilized in the potential treatment of ophthalmic diseases. Antagonists of P2X7 receptors prevented ATP-induced neuronal apoptosis in glaucoma, DR, and age-related macular degeneration (AMD); the A 1 receptor agonists lowered intraocular pressure in glaucoma; the A 2A receptor agonists or antagonists reduced neuroinflammation in glaucoma, DR, and AMD; the A 3 receptor agonists protected retinal ganglion cells (RGCs) from apoptosis in glaucoma [96]. Since the A 1 , A 2A , and A 3 receptor were concerned in ophthalmic diseases, and it should be taken into consideration that whether this purinergic signalling was modulated by miRNAs or not.…”
Section: Purinergic Signalling Modulated By Mirnas In Ophthalmic Diseasesmentioning
confidence: 99%
“…However, in neurodegenerative diseases, purinergic signaling becomes dysregulated, and significant amounts of various purine nucleotides are released into the extracellular matrix [ 151 ]. These purine nucleotides are also potent extracellular signaling molecules that can induce purinergic signaling pathways via activation of purinoceptors P1 and P2 that elicit a variety of pathophysiological pathways in the retina contributing to three types of blinding diseases including AMD, diabetic retinopathy, and glaucoma [ 152 ]. Recent studies identified a special sub-type of macrophages, capillary-associated microglia, which through P2Y purinoceptors regulate neurovascular structure and function [ 153 ].…”
Section: Choriocapillaris In Early Amdmentioning
confidence: 99%